PRODUCTION AND CHARACTERIZATION OF CRUDE INTRACELLULER PHYTASE FROM RECOMBINANT BACTERIA pEAS1AMP - Nuhriawangsa, A.M.P.; Bachruddin, Z.; Sajidan, S.; Wibowo, A. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
This research was aimed at producing a crude intracellular phytase characterized from recombinantbacteria. The recombinant bacteria (pEAS1AMP) was produced by way of transforming pET-22b(+)+pEAS1 into competent E. coli BL21 and E. coli BL21(DE3) cells. Crude intracellular phytaseproduction was induced using 1,5 mM Isopropyl-β-D-thiogalactopyranosid (IPTG). Recombinantbacteria product and enzyme activity test followed the Sajidan method. E. coli BL21(+)pEAS1 and E.coli BL21 (DE3)(+)pEAS1 recombinant bacteria showed growth after 20 hours and 10 hours oftransformation. Phytase activity of E. coli BL21 (DE3)(+)+pEAS1 showed higher than those of E. coliBL21(+)+pEAS1. Crude intracellular phytase of pEAS1AMP recombinant bacteria has an optimumactivity at pH 5, 40oC, incubation period of 60 minutes, substrate concentration of 2%, molecular weight(MW) of 47.3 kDa, Km = 15.91 υM and Vm = 2.41 υM/second. Mg2+ acts as a cofactor but Fe3+ (10-4M) acts as an inhibitor.